Methodical Conditions for Increasing the Indicators of Technique on the Basis of Special Physical Training of Young Squash Players - Artemii Perun; Rehina Andrieieva; Viktoria Koval; Oksana Shvets (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2018)
Current physical and technical preparation of young squash players and their coordination were evaluated during formative experiment. Experimental study was carried out from September 2016 to May 2017. Twelve squash players of 9–11 years old (4 young squash players of 9 years old, 10 years old and 11 years old, respectively) participated in the studies, which were conducted on the basis of Fitness club «Sport-Life» in Kherson. All squash players belonged to the main medical group. For the purpose of qualitative organization of experimental research, we chose a method of analysis and synthesis of scientific and methodological data, special and informative sources, methods of monitoring the organization of training process, methods of pedagogical testing, and methods of mathematical statistics (calculated methods of average and false values, percent values, and method of correlation analysis). Results of the previous research on preparation of young athletes, conducted by us at the beginning of preparatory period, allowed indicating characteristic indices for the majority of young athletes that were below middle level. The number of athletes with the middle level of physical and technical preparation increased considerably after the formative experiment. Due to the obtained data it was possible to state high efficiency in elaborated by us program for training session at the stage of initial preparation of young squash players. The analysis made does not cover all aspects of solving the problem in question. Further study presupposes the investigation of the influence of squash training on various indicators of the physical condition of squash players, the analysis of the indicators of training and competitive activity of squash players, in the context of revealing their leading and indifferent physical qualities.